Development of flat absorber black anodic coating on 3D printed Al–10Si–Mg alloy for spacecraft thermal control application. Issue 23 (1st December 2022) - Ghosh, Rahul; Dey, Arjun; Kavitha, M.K.; Thota, Hari Krishna; Rani, R. Uma; Rajendra, A.; Das, Karabi
Abstract: Black anodic coating (BAC) is developed on 3D printed or additively manufactured (AM) Al–10Si–Mg alloy by sulphuric acid based anodization technique at low (∼9 °C) temperature. The microstructural and surface properties of the coating are investigated by optical microscopy (OM), scanning electron microscopy (SEM), atomic force microscopy (AFM), X-ray diffraction (XRD) and water contact angle (WCA) measurement techniques. The solar absorptance and infrared (IR) emittance of the coating have been evaluated in the range 200–2500 nm and 3–30 μm, respectively. Nanoindentation technique is employed with low load to evaluate the hardness and modulus of the coating at microstructural length scale. The anodic coating shows superior hardness (∼3.95 GPa) and modulus (∼96 GPa) as compared to reported literature values, possibly due to dense microstructure and the presence of harder ceramic phases, e.g., alumina and kyanite in anodic coating. Further, due to dense microstructure, corrosion resistance improves significantly after anodization of AM alloy. Finally, thermo-optical properties are not altered after the space environmental tests which ensures the usage of the present anodic coating on AM Al alloy for spacecraft thermal control application. The solar absorptance (0.87) and IR emittance (0.78) obtained for the present coating as flat absorber characteristics are higher than the coatings processed on conventional wrought alloys. The present anodic coating shows substantial improvement in mechanical, thermo-optical and corrosion properties due to higher silicon content unlike conventional wrought alloy and refinement in microstructure during additive manufacturing aiding continuous and uniform anodic oxide layer.